No Significant Cytotoxic Effect of the EZH2 Inhibitor Tazemetostat (EPZ-6438) on Pediatric Glioma Cells with Wildtype Histone 3 or Mutated Histone 3.3 - Wiese, M.; Schill, F.; Sturm, D.; Pfister, S.; Hulleman, E.; Johnsen, S. A.; Kramm, C. M. (Klinische Pädiatrie, 2016)
Background: Glioblastoma multiforme (GBM) and diffuse intrinsic pontine glioma (DIPG) belong to the most aggressive cancers in children with poor prognosis and limited therapeutic options. Therapeutic targeting of epigenetic proteins may offer new treatment options. Preclinical studies identified Enhancer of Zeste Homolog 2 (EZH2) within polycomb repressor complex 2 (PRC2) as a potential epigenetic anti-tumor target in adult GBM cells but similar inhibition studies in pediatric GBM/DIPG were still missing. Moreover, approximately 30% of pediatric high grade gliomas (pedHGG) including GBM and DIPG harbor a lysine 27 mutation (K27M) in histone 3.3 (H3.3) which is correlated with poor outcome and was shown to influence EZH2 function.Patients, materials and methods: The present study investigated the correlation of expression of EZH2 and other PRC2 genes (EZH1, SUZ12, EED) with overall survival of pediatric GBM patients and the cytotoxic impact of EZH2 inhibition by the novel agent Tazemetostat in pediatric GBM/DIPG cells harboring either a H3.3 mutation or a H3 wildtype.Results: EZH2 gene expression does not correlate with survival of pedHGG patients, and EZH2 inhibition does not induce significant cytotoxicity in pedHGG cells independently of H3.3 mutations.Discussion and conclusion: We suggest that EZH2 inhibition might not offer an effective single agent treatment option for paedHGG patients. However, the therapeutic efficacy in combination with cytotoxic and/or other epigenetically active agents still has to be elucidated.
Keywords: EZH2 inhibition; Tazemetostat (EPZ-6438); cancer epigenetics; histone 3 mutation; pediatric high-grade glioma (pedHGG)